Hubungan Aktivitas Fisik dengan Status Gizi Berdasarkan IMT/U Siswa Kelas XI SMA di Palembang - Rafaely Audrey Nurmarina Dwinovary; Dheni Koerniawan (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Physical activity is one of the factors that affect the nutritional status of adolescents. Lack of physical activity will lead to excess weight. The purpose of this study is to analyze the relationship between physical activity and nutritional status of eleventh grade students in high school in Palembang. This quantitative research uses a cross-sectional research design with a sample of 91 students. Physical activity was measured using the Adolescent-Physical Activity Questionnaire (PAQ-A). The nutritional status used is based on BMI/age. The correlation analysis used was Kendall's tau-b. Univariate results were obtained by the majority of students with low physical activity (f=40) and normal nutritional status (f=60). Based on the results of the correlation test, a p-value of 0.004 < 0.05 was obtained, which means that there is a significant relationship between physical activity and nutritional status based on BMI/U. With a correlation coefficient of 0.276, which means that the correlation strength is low with positive traits. Based on the results of the study, it is recommended that adolescents do enough physical activity to maintain physical fitness and health as well as normal nutritional status.